Trust in virtual reality - Salanitri, Davide (2018)
The current era has seen unrestrained technological progress. New technologies are replacing common work practices and processes in several fields, such as industry, healthcare, and commerce. The main reasons for using these technologies is the reduction of time to develop products, increased quality of products and processes, and increases in security and communication. This thesis focuses on Virtual Reality (VR). VR is currently replacing old systems and modifying practices and processes in fields such as automotive, healthcare, training and psychological therapies. However, when applying technologies, it is fundamental to study the interaction between the technology and the end users. This thesis takes into consideration one aspect of human-computer interaction: trust. Trust has been seen as fundamental in technologies such as e-commerce, e-marketing, autonomous systems and social networks. This is because trust has been found to be associated with the intention to use a technology, and lack of trust could deter users from adopting the technology. This concept is particularly important for VR, since it is only recently gaining widespread adoption. However, studies on users’ trust in VR systems are limited in the literature and there is uncertainty regarding the factors which could influence end user trust. This research aimed at developing a model to investigate trust in VR. The goal was to identify the factors which have a theoretical influence on trust in VR through an analysis of the literature on trust in VR and trust in technology in general. This permitted the creation of a framework with usability, technology acceptance and presence as possible predictors of trust in VR. In order to validate this framework, six user experiments were conducted. The experiments investigated the relationships among the factors identified in the literature and their influence on trust. The first study was designed to explore possible methodological issues. The next three studies, conducted in collaboration with researchers at the University of Nottingham, analysed further the relationship between usability and trust and between technology acceptance and presence with trust. The fifth experiment was conducted to specifically explore the influence of presence on trust. The last study looked at all factors, and validated the framework, demonstrating that technology acceptance and presence are predictors of trust in VR, and usability has an indirect effect on trust, as it is a strong predictor of technology acceptance. This research generated a model which includes well-studied factors in human computer interaction and human factors and could be applied to study trust in VR for different systems. This model increases the amount of information on VR, both on an academic and industrial point of view. In addition, guidelines based on the model were generated to inform the evaluation of existing VR systems and the design of new ones.